2011
DOI: 10.1080/15374416.2011.581622
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Adaptation to Poverty-Related Stress Model: Predicting Psychopathology Symptoms in Families Facing Economic Hardship

Abstract: This study tested the Adaptation to Poverty-related Stress Model and its proposed relations between poverty-related stress, effortful and involuntary stress responses, and symptoms of psychopathology in an ethnically diverse sample of low-income children and their parents. Prospective Hierarchical Linear Modeling analyses conducted with 98 families (300 family members: 136 adults, 82 adolescents and preadolescents, 82 school-age children) revealed that, consistent with the model, primary and secondary control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
80
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 37 publications
8
80
0
3
Order By: Relevance
“…This coincides with previous data regarding stressors and internalizing an externalizing problem [22,50,52]. The difference between youth risk, for instance, with or without suicidal ideation [53], drug consumers or nonconsumers [54] and adolescents with or without psychopathology [55] is the number, type, and source of stressors, generally related to family, in which, even normative life events, can be perceived negatively by adolescents [46].…”
Section: Stress Life Events and Coping In Disadvantaged Communitiessupporting
confidence: 66%
See 2 more Smart Citations
“…This coincides with previous data regarding stressors and internalizing an externalizing problem [22,50,52]. The difference between youth risk, for instance, with or without suicidal ideation [53], drug consumers or nonconsumers [54] and adolescents with or without psychopathology [55] is the number, type, and source of stressors, generally related to family, in which, even normative life events, can be perceived negatively by adolescents [46].…”
Section: Stress Life Events and Coping In Disadvantaged Communitiessupporting
confidence: 66%
“…Economic pressure represents a chronic stressor associated to mental health problems including anxiety and depression. Therefore, it supports the notion of relationship between economic hardship, family conflict, and emotional disorder [17,22].…”
Section: Stress Life Events and Coping In Disadvantaged Communitiesmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, several studies have highlighted the deleterious effects of poverty-related stress [11, 12], marital conflict [13, 14], family aggression [15], and child maltreatment [16] on child and adolescent emotional and behavioral outcomes. Specific to the family context, research has shown that measures of chronic family stress and cumulative stressful family life events (sometimes referred to as adversity or adverse life events ) are also related to child and adolescent problem behaviors.…”
Section: Stressful Family Life Events and Adolescent Problem Behaviorsmentioning
confidence: 99%
“…This disadvantage may stem broadly from lack of parent involvement and availability (Cooper & Crosnoe, 2007;Harris & Marmer, 1996;Olsson, 2009;Pittman & Chase-Lansdale, 2001;Ryan, Miller-Loessi, & Nieri, 2007). More specifically, difficult or tenuous parentchild relationships among low SES youth are often linked to parental stress, distress, and depression (Prelow, Weaver, Bowman, & Swenson, 2010;Wadsworth, Raviv, Santiago, & Etter, 2011). Relational problems also arise from parents' perceived isolation and lack of support (Middlemiss, 2003;Raikes & Thompson, 2005).…”
mentioning
confidence: 95%